Mucosal subepithelial binding sites for the bacterial chemotactic peptide, formyl-methionyl-leucyl-phenylalanine (FMLP). Issue 3 (1st March 1998) - Anton, P; O'Connell, J; O'Connell, D; Whitaker, L; O'Sullivan, G C; Collins, J K; Shanahan, F
Abstract : Background —The bacterial chemotactic peptide N- formyl-methionine-leucine-phenylalanine (FMLP) is produced by enteric flora and is one of the factors implicated in contributing to inflammatory bowel disease. Expression of receptors for FMLP on human phagocytes (polymorphs and monocytes) is well established, but there is conflicting evidence regarding the potential expression of FMLP receptors on other cells within the mucosa, particularly the epithelial cells. Aims —To map FMLP receptors within intestinal mucosa using several different experimental approaches. Methods and results— Radioligand binding assays with 3 H-FMLP revealed no specific binding to primary cultured colonic enterocytes or to the cell line HT29, whereas neutrophils, as expected, exhibited specific binding with a Kd of 19 nM and approximately 2 × 10 4 receptors per cell. FITC labelled FMLP exhibited specific, displaceable binding on flow cytometry to neutrophils and monocytes but not to 10 gastrointestinal epithelial cell lines. Isolated lamina propria lymphocytes and peripheral blood lymphocytes exhibited no binding. To confirm the absence of receptors on epithelia, reverse transcription polymerase chain reaction for mRNA for the classic FMLP receptor was performed. While the presence of message was detected in activated peripheral blood phagocytes, it was not detected in epithelial cell lines. To exclude the possibility of FMLP binding to other receptors such as tachykinin receptors on epithelia, FITC labelled FMLP binding in tissue sections confirmed that the binding is subepithelial—that is, in the lamina propria. Conclusion —Receptors for FMLP are subepithelial and map to the lamina propria of the gastrointestinal mucosa.